Evolution of Surgical Management of Sagittal Synostosis. Issue 1 (January 2021) - Bradford, Perry S.; Ishaque, Mariam; Shaffrey, Ellen; Schaeffer, Christine V.; Jr, John A. Jane; Syed, Hasan; Black, Jonathan
Abstract : Abstract: Numerous methods for surgical correction of sagittal synostosis have been described in the literature, yielding similar outcomes. At the authors' institution, surgical approaches to correct this condition have evolved over the past few decades, including Π, H-type craniectomies (Renier), endoscopic suturectomy, and our current technique, the FLAG procedure. Our aim is to review the evolution of these surgical techniques at our institution and compare patient outcomes. A retrospective review was performed on consecutive patients undergoing correction for craniosynostosis from 2008 to 2018. All patients with a diagnosis of nonsyndromic isolated sagittal craniosynostosis were included and classified into one of 4 groups by the type of surgical correction performed (H-type, FLAG, endoscopic, other). The authors identified 166 consecutive patients with a mean age at time of surgery of 6.7 ± 4.0 months. 91 (54.8%) carried a diagnosis of nonsyndromic sagittal synostosis. 63 patients underwent H-type procedures, 9 underwent FLAG procedures, 5 underwent endoscopic procedures, and 14 were classified as other (distraction or other implant). Perioperatively, the FLAG group had the shortest ICU stay (1.3 days, P < 0.05), postoperative transfusion requirement (42cc pRBC, P < 0.001), and complication rate (0.0%). The endoscopic group had the shortest surgical time at 2.00 hours (p < 0.001). No statistically significant difference in cranial index or revision procedures between the four groups was identified. Overall, the mean length of follow-up was 25.3 months. All procedures had similar results for cranial index with decreased surgical time, transfusion volume, and hospital stay seen in FLAG and endoscopic groups. Abstract : Supplemental Digital Content is available in the text